Potential Side Effects of Orthodontic Treatment and Avoiding "Malpractice Claims" - Selin Kale (Galenos Yayinevi, 2006)
Orthodontic treatment involves application of a wide range of procedures that can have local or in some instances systemic effects. Despite the lack of sound evidence of a direct relation between orthodontic treatment and specific pathologic conditions, malpractice claims involving TMJ dysfunctions, periodontal problems, alveolar bone loss, root resorption are increasing. The purpose of this article is to briefly discuss a number of pathologic conditions that have been assigned to orthodontics, summarize the basic information needed to minimize or avoid malpractice claims and explain the article of new Turkish Penal Code related to health issues.